Development of Didactic Design for Learning Mathematics in Pesantren: Integration of Mathematics and Fiqh Learning - Sendi Ramdhani; Didi Suryadi; Sufyani Prabawanto (Institut Pendidikan Indonesia Garut, 2023)
Perlu dikembangkan model pembelajaran matematika di pesantren yang dikaitkan dengan permasalahan yang sesuai dengan situasi di pondok pesantren, misalnya terkait dengan fiqh. Penelitian ini menggunakan Design Didactical Research (DDR). Pengembangan desain didaktis ini dilakukan dengan menggunakan Theory of Didactical Situation (TDS). Pembelajaran matematika di pesantren dirancang sebagai berikut: pembacaan ayat suci Al-Qur'an dan Hadits terkait materi pembelajaran matematika; materi dan tujuan pembelajaran yang terkait dengan ilmu keislaman; dan memberikan gambaran tentang manfaat mempelajari materi yang akan dipelajari dalam kehidupan sehari-hari, terutama ketika nantinya menjadi kader ulama. Pengembangan desain didaktis didasarkan pada teori situasi didaktis, yaitu: Situasi Devolusi, santri diberikan tantangan untuk menyelesaikan masalah zakat dan waris; Situasi Matematis, santri yang belum mampu menyelesaikan tantangan utama dibimbing melalui soal, tabel, dan petunjuk. Demikian pula santri yang sudah memiliki tebakan pemecahan masalah terus melakukan langkah-langkah untuk menguji keabsahan asumsi tersebut dengan menjawab beberapa pertanyaan, memperhatikan tabel, dan melaksanakan instruksi; Situasi Kelembagaan, santri membuat kesimpulan dengan bimbingan guru tentang poin-poin penting.It is necessary to develop a mathematics learning model in pesantren that is associated with problems that are following the situation in the Islamic boarding school, for example, related to fiqh. This study used Design Didactical Research (DDR). The development of this didactic design was carried out using the Theory of Didactical Situation (TDS). The learning mathematics in pesantren is designed as follows: reading of the holy verses of Al-Qur'an and Hadith related to mathematics learning materials; the material and learning objectives associated with Islamic knowledge; and giving an overview of the benefits of studying the material to be studied in everyday life, especially when later becoming a cadre of the ulama. Didactic design development is based on the theory of didactic situation, namely: In the case of Devolution, santri are given the challenge of solving zakat and inheritance problems; in Mathematical Situations, santri who have not been able to complete the main difficulties are guided through questions, tables, and instructions. Likewise, santri, who already has problem-solving guesses, continues to test the validity of these assumptions by answering several questions, paying attention to tables, and carrying out instructions; 3) Situation of Institutionalization, santri makes conclusions with teacher guidance about essential points.